Building Bridges from Theory to Practice - Dumais, Susan; Czerwinski, Mary (2001)
The bridges from basic cognitive theory to applied human-computer interaction practice are neither as strong nor as complete as we would like to see. This paper outlines some areas in which the two disciples of complement each other. We also describe several challenges such as designing from first principles, generating useful results and guidelines, and moving professionally between the two disciplines. Although much progress has been made in the last few decades, we believe that both disciplines can benefit from a closer partnership, and we hope that this panel begins to build some of these bridges.
HCI International 2001, 9th Conference on Human-Computer Interaction. Session on Contributions of Basic Research in Psychology to Human Factors and Human-Computer Interaction.